2021
DOI: 10.18609/cgti.2021.133
|View full text |Cite
|
Sign up to set email alerts
|

The UK’s emerging regulatory framework for point-of-care manufacture: insights from a workshop on advanced therapies

Abstract: Point-of-care (POC) manufacture can be defined as the production of therapies in clinical settings or units close to hospitals and patients. This approach is becoming increasingly viable due to the emergence of flexible manufacturing technologies. Expecting an increase in this kind of production, the UK's regulatory agency, the Medicines and Healthcare products Regulatory Agency (MHRA) is proposing a regulatory framework specifically designed for POC manufacture. To discuss the challenges of POC manufacture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Together, these four countries are a good illustration of the interplay between unifying concepts versus national differences in the way ATMP-HE are managed in different healthcare systems. Footnotes to Table 5 cite the breakdown of these parameters in previous studies of ATMP-HE practices in Europe ( 3 15 ). It is worth pointing out that many aspects of healthcare in general are not fully harmonized at the EU level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Together, these four countries are a good illustration of the interplay between unifying concepts versus national differences in the way ATMP-HE are managed in different healthcare systems. Footnotes to Table 5 cite the breakdown of these parameters in previous studies of ATMP-HE practices in Europe ( 3 15 ). It is worth pointing out that many aspects of healthcare in general are not fully harmonized at the EU level.…”
Section: Discussionmentioning
confidence: 99%
“…To date there is no full harmonization of ATMP-HE regulations among EU countries, beyond the overall guidelines provided in the original EU regulation that created ATMP-HE ( 2 – 15 ). We have demonstrated that the Polish implementation of the EU directive is within the mainstream of practices among EU countries regarding manufacturing of products and management of ATMP-HE programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, due to the autologous nature of many of these cell-based products, process-related adaptations have been made to the ad hoc manufacturing workflows, to optimally account for the short shelf-life and the volatile nature of the processed biological materials [16]. Due to burdening temporal and logistical constraints, several initiatives for point-of-care manufacturing of cell-based therapeutic products have emerged, which imply small-batch processing and multi-professional specific expertise [17]. Alternatively, several cost rationalization drivers have led to the emerging technological transition toward mobile infrastructures and automated bioreactor systems, for the insurance of both flexibility and efficiency of the GMP-compliant cell production [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%